Early developmental stress negatively affects neuronal recruitment to avian song system nucleus HVC. Issue 1 (1st June 2015) - Honarmand, Mariam; Thompson, Christopher K.; Schatton, Adriana; Kipper, Silke; Scharff, Constance
ABSTRACT: Adverse environmental conditions can impact the life history trajectory of animals. Adaptive responses enable individuals to cope with unfavorable conditions, but altered metabolism and resource allocation can bear long‐term costs. In songbirds, early developmental stress can cause lifelong changes in learned song, a culturally transmitted trait, and nestlings experiencing developmental stress develop smaller song control nucleus HVCs. We investigated whether nutrition‐related developmental stress impacts neurogenesis in HVC, which may explain how poor nutrition leads to smaller HVC volume. We provided different quality diets (LOW and HIGH) by varying the husks‐to‐seeds ratio to zebra finch families for the first 35 days after the young hatched (PHD). At PHD14–18 and again at nutritional independence (PHD35), juveniles were injected with different cell division markers. To monitor growth, we took body measures at PHD10, 17, and 35. At PHD35 the number of newly recruited neurons in HVC and the rate of proliferation in the adjacent ventricular zone (VZ) were counted. Males raised on the LOW diet for their first weeks of life had significantly fewer new neurons in HVC than males raised on the HIGH diet. At the time when these new HVC neurons were born and labeled in the VZ (PHD17) the birds exposed to the LOW diet had significantly lower body mass. At PHD35 body mass or neuronal proliferation no longer differed. Our study shows that even transitory developmental stress can have negative consequences on the cellular processes underlying the development of neural circuits. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 76: 107–118, 2016